THE EFFECTIVENESS OF COMMUNITY-BASED THERAPY IN RE-LEARNING SOCIAL SKILLS AMONG ADULTS LIVING WITH TRAUMATIC BRAIN INJURY: A CRITICALLY APPRAISAL TOPIC - Obisike, Ebere Ellison; Adalikwu-Obisike, Justina (European Scientific Journal, ESJ, 2012)
This study critically appraised peer reviewed journal articles to investigate the success of community-based therapy in re-learning social skills among adults with traumatic brain (TBI) injuries. Data were collected using the following databases: Psychinformation; Pubmed; Medline; Proquest; CINAHL; OT seeker and the Cochrane Library. Four journal articles that met the inclusion criteria were selected for final appraisal. While all the selected appraised studies support the assertion that community-based therapy is effective in aiding adults with TBI in re-learning their social skills, they also suggested that this approach to care should not be used in isolation of other care methods.